Efektivitas Air Cucian Beras Dan Ekstrak Daun Kelor Untuk Pertumbuhan Tanaman Cabai Merah (Capsicum annum L.) Dengan Teknik Hidroponik - Astuti, Fitri; Asngad, S.Si, M.Si, Dra.Aminah Asngad, S.Si, M.Si (2016)
Hydroponics is a technique of plant cultivation without using soil, but water as the plantation media. Rice washing water can be used as the growth nutrition for plants because it contains NPK nutrients and bacteria Pseudomonas fluorescens are used as raw materials in a liquid organic fertilizer. Moringa leaves extract can be used to hasten the plant's growth naturally. Pepper is a plant that is needed by the whole citizen especially in household. The aim of this research is to reveal the red pepper's growth by using different media and nutrition, and to understand the interaction between them. This research has two factors. First the media are M1 (rockwool) and M2 (coconut fiber). Second, the nutritions are N1 (rice washing water 100%), N2 (moringa leaves extract 40%), also N3 (mixture of rice washing water and moringa leaves extract 50% : 50%). The result shows that the treatment is effective M1N1 (rockwoll media with rice washing water nutrition 100%) on the growth of plant height 4,63 cm, leaves's area 0,93 cm2 and length of root 2,60 cm.